2008
DOI: 10.1145/1453175.1453182
|View full text |Cite
|
Sign up to set email alerts
|

How to parameterize models with bursty workloads

Abstract: Although recent advances in theory indicate that burstiness in the service time process can be handled effectively by queueing models (e.g., MAP queueing networks [2]), there is a lack of understanding and of practical results on how to perform model parameterization, especially when this model parameterization must be derived from limited coarse measurements as is often encountered in practice. We propose a new modeling methodology based on the index of dispersion of the service process at a server, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…[7] introduces the concept of characterizing burstiness in time series of workload arrivals using the index of dispersion. In [8], [9] the authors describe how the index of dispersion can be used to model and parametrize bursty workloads when investigating service times in multi-tier applications. [10] presents Fasttrack, a dynamic resource provisioning solution for multi-tiered applications that estimates the index of dispersion and utilizes it for determining when the workload is entering and exiting a bursty state.…”
Section: Related Workmentioning
confidence: 99%
“…[7] introduces the concept of characterizing burstiness in time series of workload arrivals using the index of dispersion. In [8], [9] the authors describe how the index of dispersion can be used to model and parametrize bursty workloads when investigating service times in multi-tier applications. [10] presents Fasttrack, a dynamic resource provisioning solution for multi-tiered applications that estimates the index of dispersion and utilizes it for determining when the workload is entering and exiting a bursty state.…”
Section: Related Workmentioning
confidence: 99%
“…Casale et al [7] showed how to incorporate burstiness into the analytical queuing network models. These approaches provide sound foundational basis for medium term or offline capacity estimation, in contrast to our adaptive approach based on measured performance.…”
Section: Related Workmentioning
confidence: 99%
“…Temporal burstiness is the tendency of job arrivals to occur in clusters, or bursts, separated by long periods of relatively few or no arrivals [10], [19]. In fact, there always exist bursts in real workloads due to the occurrence of bags-of-tasks and idle periods during nights, weekends, holidays, etc.…”
Section: B Temporal and Spatial Burstinessmentioning
confidence: 99%